Consumers wine preferences according to purchase occasion: Personal consumption and gift-giving - Boncinelli, Fabio; Dominici, Andrea; Gerini, Francesca; Marone, Enrico (Food quality and preference, 2019)
•Consumers value brand and designation of origin for their personal consumption.•Consumers’ value organic status and brand in a gift-giving scenario.•Demand for wine is less reactive to price changes in a gift-giving scenario.•We found three groups of consumers: brand follower, organic supporter, and unyielding. We tested the hypothesis that individuals may act differently when buying a bottle of wine for themselves than they do when buying wine as a gift. Using a between-subject design, we estimated the differences in consumer preference for these two occasions. We conducted a choice experiment on 618 Italian wine consumers and included the attributes of price, geographical indication (i.e. IGT, DOC, or DOCG), organic claim, and brand (i.e. famous producer or a non-famous producer). By applying an error component random parameters logit model, we detected relevant differences between the two scenarios in terms of the relative importance of the studied attributes. The gift-giving scenario was further investigated using a latent class model, which identified three segments of consumers; we profiled these according to personal attitudes and wine knowledge. Our results show a relevant heterogeneity among consumers’ preferences for the gift-giving scenario, with geographical indication having a low impact and brand and organic claim playing a pivotal role. This study provides relevant insights for winemakers and retailers regarding diversifying marketing strategies.